Work in progress - learning through role play games - Baptista, Ricardo (2014)
It is commonly accepted that the educational environment has been undergoing considerable change due to the use of the Information and Communication tools. But learning depends upon actions such as experimenting, visualizing and demonstrating through which the learner succeeds in constructing his own knowledge. Although it is not easy to achieve these actions through current ICT supported learning approaches, Role Playing Games (RPG) may well develop such capacities. The creation of an interactive computer game with RPG characteristics, about the 500th anniversary of the city of Funchal, the capital of Madeira Island, is invested with compelling educational/pedagogical implications, aiming clearly at teaching history and social relations through playing. Players interpret different characters in different settings/scenarios, experiencing adventures, meeting challenges and trying to reach multiple and simultaneous goals in the areas of education, entertainment and social integration along the first 150 years of the history of Funchal. Through this process they will live and understand all the social and historical factors of that epoch.